Arabic Language in the Representation of Digital Communication Through WhatsApp Stickers - Shofuro Zamzamy Ulin Najwa; Majda Qudsiyatul Malikh; Muhammad Arsy Alghiffari (STIQ Amuntai, 2026)
The development of digital communication has transformed how students express meaning, emotions, and cultural values in academic interactions. In this context, the use of Arabic-language stickers in WhatsApp has emerged as a linguistic phenomenon that integrates verbal, visual, and religious elements in student academic communication. This study employs a qualitative approach with thematic analysis to examine the meanings and communicative functions of Arabic stickers in students’ WhatsApp conversations. The data consist of screenshots of interactions between students and lecturers using stickers such as Fi Amanillah, Maas Salamah, and Kullu ‘am wa antum bi alfi khair. The findings show that Arabic stickers function not only as visual elements but also as a medium for expressing religiosity, politeness, and academic solidarity, and as a substitute for nonverbal cues in digital communication, enabling messages to be conveyed concisely, effectively, and with pragmatic and cultural depth. These findings highlight the integration of digital linguistics, language pedagogy, and academic communication, where Arabic stickers represent multimodal language resources that expand meaning-making in virtual spaces, can be utilised as context-based Arabic learning media to enhance pragmatic and cultural competence, and contribute to the development of communication ethics, social closeness, and interaction efficiency in Islamic higher education environments. Thus, this study explicitly contributes to digital linguistics through multimodal discourse analysis of online communication, to language pedagogy through implications of digital-based Arabic learning, and to academic communication through the reinforcement of polite, meaningful, and effective interaction in digital academic settings.